Penyelesaian Wanprestasi Kredit Multiguna Dengan Jaminan Surat Kepemilikan Kendaraan Bermotor (Studi Kasus Di BPR Surasari Hutama Cabang X) - Bara Abdul Gani; Mas Anienda Tien Fitriyah (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
Credit in Article 11 of Law Number 10 of 1998 refers to the provision of money or the equivalent thereof in the form of a bill, based on the agreement and mutual understanding between the two parties, namely the Debtor and the Creditor, with the obligation for the Debtor to repay the debt and interest obligations that have been determined. Before credit is granted to the debtor, the creditor will conduct a field survey regarding the debtor's financial activities until all conditions are deemed fulfilled, in order to avoid default issues in the credit agreement between the two parties. There are many ways to resolve default cases, and in BPR Surasari Hutama, resolving default issues in Credit Agreement No. B.28613/2019 that occurred in March 2019 with the guarantee of ownership documents of a 2005 Hyundai Excel motor vehicle was done by providing a multipurpose credit loan of Rp 15,000,000. It can be said that the loan became delinquent because the debtor did not have good intentions to repay the debt, resulting in an outstanding balance of Rp 9,800,000, and fled with the object provided as collateral. This study aims to understand the resolution of default in Multipurpose Credit with Motor Vehicle Ownership Documents as collateral and to determine that the creditor does not immediately execute the object but rather issues verbal or written reminders, such as Collection Letters or Warning Letters, in accordance with Bank Indonesia Circular Letter No. 26/4/BPPP dated May 29, 1993, and adheres to OJK regulations and Bank Indonesia Regulation No. 7/2/PBI/2005 dated January 20, 2005 regarding Restructurable Banking Credit.